Four Atmospheric Circulation Regimes Over the North Pacific and Their Relationship to California Precipitation on Daily to Seasonal Timescales. Issue 16 (11th August 2020) - Guirguis, Kristen; Gershunov, Alexander; DeFlorio, Michael J.; Shulgina, Tamara; Delle Monache, Luca; Subramanian, Aneesh C.; Corringham, Thomas W.; Ralph, F. Martin
Abstract: Precipitation in California is highly variable and not well forecasted on subseasonal‐to‐seasonal (S2S) timescales. Understanding relationships between synoptic‐scale atmospheric circulation and hydrometeorological extremes could improve predictability. This work demonstrates the importance of four North Pacific circulation regimes (called the NP4 modes) in modulating precipitation, flooding, and water resources in California. Here we demonstrate how, on daily timescales, interactions between the NP4 modes drive coastal flow that can result in dry conditions from atmospheric ridging or wet conditions associated with enhanced onshore flow and atmospheric river (AR) landfalls. Seasonally, the prevalence of certain NP4 phase relationships can tip the scale toward wet or dry conditions. Relationships between El Niño Southern Oscillation (ENSO) and the NP4 are explored, and we provide insight into the poorly forecasted Western US seasonal precipitation during the "Godzilla" El Niño winter of 2016 by examining climate‐weather linkages in a historical context. Plain Language Summary: The amount of precipitation that falls over California in a given water year is highly variable, which presents challenges for water resource management. Skill of both dynamical and statistical models in forecasting precipitation is low at lead times beyond 2 weeks. Recent research has explored relationships between atmospheric circulation patterns and precipitation extremes in the western United States, with the goal of improving predictability. This work demonstrates the importance of four North Pacific circulation regimes in modulating coastal flow patterns that ultimately determines the amount and spatial distribution of precipitation over California on daily and seasonal timescales. We show how the interaction between these modes on daily timescales drives wet and dry episodes within a season. Seasonally, we show how the daily variability occurs within certain constraints established by the larger, more slowly varying climate system, including (but not limited to) El Niño‐Southern Oscillation. This work improves understanding of climate‐weather relationships, which has implications for predictability of hydrometeorological extremes over California and the western United States. Key Points: Coastal vapor transport and California precipitation are modulated by four North Pacific circulation regimes on daily to seasonal timescales The most damaging California floods have occurred when these modes were jointly aligned to reinforce onshore flow Seasonally, these modes are influenced by ENSO but much variability occurs within the constraints set by the larger‐scale climate system